MOTIF KEBUTUHAN DAN PERTUMBUHAN ROHANI PELAYAN JEMAAT - Jonathans, Kornelius Rulli (The Way: Jurnal Teologi dan Kependidikan, 2024)
The purpose of this study was to determine the effect of Need Motives on the Spiritual Growth of congregational servants. The need motives studied include high-level needs such as being loved and loving, being appreciated and appreciating, and self-actualization, which are compared with low-level needs, namely physiological and security. Using the Slovin formula and α = 5%, the researcher determined a sample of 80 respondents from a population of 100 congregational servants. This study uses a quantitative method with regression analysis to measure the effect of the Need Motive variable (X) on Spiritual Growth (Y). The results of the analysis show a regression equation Ŷ = 91.960 + 1.357X, with a correlation coefficient of 0.567 and a determination coefficient of 0.321 at a significance level of 5%. The regression coefficient of 1.357 indicates that there is a positive influence between Need Motives and Spiritual Growth. The interpretation of these results shows that congregational servants who have met high-level needs are better able to achieve better spiritual growth. In conclusion, the need motive plays a significant role in supporting the spiritual growth of congregational servants.